Game interruptions in elite soccer - Siegle, M.; Lames, M. (Journal of Sports Sciences, 2012)
The objectives of the study were to analyse game interruptions of league soccer in detail and the tactical use of game interruptions. Sixteen matches of a German first league soccer team were observed. An observational system was designed to assess interruption types, score, duration of interruption, location of interruption, time of interruption and number of occurrences. Results showed that there is an average of 108 interruptions per match. Throw-ins (40) and free kicks (33) were most frequent. Goal kicks (17), corner kicks (10), substitutions (4), and kick offs (3) occurred less often. Drop balls, penalties, and injuries occurred least often. For 38% of the total match time observed, matches were halted. The mean duration of running and interrupted match parts were 32.1 s and 18.7 s, respectively. The analysis showed significant differences concerning the influence of the location of interruption, score, and time of interruption on the duration of different interruption types (P < 0.05). The results of the study showed the tactical use of game interruptions during league soccer matches, e.g. goal kicks of the leading team take longer towards the end of the match. Examining game interruptions has turned out to be a valuable source of information adding to our knowledge of soccer. We have shown evidence that the durations of many interruptions serve tactical purposes, a well-known hypothesis in practice.